A phase sensitive x-ray breast tomosynthesis system: Preliminary patient images with cancer lesions. (29th October 2021) - Ghani, Muhammad U; Fajardo, Laurie L; Omoumi, Farid; Yan, Aimin; Jenkins, Peter; Wong, Molly; Li, Yuhua; Peterson, Michael E.; Callahan, Edward J; Hillis, Stephen L; Zheng, Bin; Wu, Xizeng; et al.
Abstract: Phase-sensitive x-ray imaging continues to attract research for its ability to visualize weakly absorbing details like those often encountered in biology and medicine. We have developed and assembled the first inline-based high-energy phase sensitive breast tomosynthesis (PBT) system, which is currently undergoing patient imaging testing at a clinical site. The PBT system consists of a microfocus polychromatic x-ray source and a direct conversion-based flat panel detector coated with a 1 mm thick amorphous selenium layer allowing a high detective quantum efficiency at high energies. The PBT system scans a compressed breast over 15° with 9 angular projection views. The high-energy scan parameters are carefully selected to ensure similar or lower mean glandular dose levels to the clinical standard of care systems. Phase retrieval and data binning are applied to the phase contrast angular projection views and a filtered back-projection algorithm is used to reconstruct the final images. This article reports the distributions of radiation dose versus thickness of the compressed breasts at 59 and 89 kV and sample PBT images acquired from 3 patients. Preliminary PBT images demonstrate the feasibility of this new imaging modality to acquire breast images at lower radiation dose as compared to the clinical digital breast tomosynthesis system with enhanced lesion characteristics (i.e. lesion spiculation and margins).